Bioassay-Guided Isolation and HPLC Determination of Bioactive Compound That Relate to the Antiplatelet Activity (Adhesion, Secretion, and Aggregation) from Solanum lycopersicum. (10th November 2012) - Fuentes, Eduardo; Castro, Ricardo; Astudillo, Luis; Carrasco, Gilda; Alarcón, Marcelo; Gutiérrez, Margarita; Palomo, Iván
Abstract : In seeking the functionality of foodstuff applicable to medicine, ripe tomato fruits were found to show an antiplatelet activity. Therefore, the bioactive compound was isolated, structurally identified, and studied for an inhibitory effects on platelet adhesion, secretion, and aggregation. The concentration of adenosine in ripe tomato fruits (pulp and skin extracts) and its processing by-products (paste and pomace) was determined by reversed-phase high-performance liquid chromatography (HPLC). According to platelet aggregation inhibition induced by ADP, the total extract residual was fractionated by liquid-liquid separation, obtaining aqueous, ethyl acetate and petroleum ether extracts. The aqueous extract was subjected to repeated permeation over sephadex LH-20 and semipreparative TLC. The isolate finally obtained was identified as adenosine on the basis of ESI-MS, 1 H NMR, HPLC, and UV spectra. Adenosine concentration dependently (2.3–457  μ M) platelet aggregation inhibited induced by ADP. Also, adenosine present inhibition of platelet secretion and thrombus formation under flow conditions. The quantitative HPLC analysis revealed significant amounts of adenosine in ripe tomato fruits and its processing by-products. From these results, extracts/fractions of ripe tomato fruits and their processing by-products may be referred to as functional food and functional ingredients containing a compound that inhibits platelet function with a potent preventive effect on thrombus formation, as those that occur in stroke.